Ruby Woods interviewed by Claudia Quinn-Young in the Australia 1938 oral history project - Woods, Ruby, 1895-; Quinn-Young, C. M. (Claudia M.); Australia 1788-1988: A Bicentennial History; Australia 1938 Oral History Project (1982)
Woods speaks of her family background; school and childhood memories; religion; her health; lifestyle as a young adult; skills learned at home; family lifestyle; living conditions; family relationships; class; health care; contact with Aborigines and migrants; family values.
Recorded by the Australia 1938 Oral History Project as research for the book Australians 1938 from the series Australians, a historical library.
Digital master available
Timed summary available.
Keywords: Woods, Ruby, -- 1895- -- Interviews; Adelaide (S.A.) -- Social conditions